Effect of Headgroups on Small‐Ion Permeability across Archaea‐Inspired Tetraether Lipid Membranes. Issue 24 (3rd May 2016) - Koyanagi, Takaoki; Leriche, Geoffray; Yep, Alvin; Onofrei, David; Holland, Gregory P.; Mayer, Michael; Yang, Jerry
Abstract: This paper examines the effects of four different polar headgroups on small‐ion membrane permeability from liposomes comprised of Archaea‐inspired glycerolmonoalkyl glycerol tetraether (GMGT) lipids. We found that the membrane‐leakage rate across GMGT lipid membranes varied by a factor of ≤1.6 as a function of headgroup structure. However, the leakage rates of small ions across membranes comprised of commercial bilayer‐forming 1‐palmitoyl‐2‐oleoyl‐sn‐glycerol (PO) lipids varied by as much as 32‐fold within the same series of headgroups. These results demonstrate that membrane leakage from GMGT lipids is less influenced by headgroup structure, making it possible to tailor the structure of the polar headgroups on GMGT lipids while retaining predictable leakage properties of membranes comprised of these tethered lipids. Abstract : Extremophiles require robust membranes with low ion permeability to survive in harsh conditions. These Archaea organisms achieve low membrane permeability, in part, by generating lipids with unusual structural features such as tethering of their lipid tails. A systematic study probing the effect of polar headgroups in synthetic Archaea‐inspired lipids showed little dependence of membrane leakage rates of small ions as a function of headgroup structure.